Epidemiology of basketball, soccer, and volleyball injuries in middle-school female athletes - Barber Foss, K. D.; Myer, G. D.; Hewett, T. E. (The Physician and Sportsmedicine, 2014)
Background:An estimated 30 to 40 million school children participate in sports in the United States; 34% of middle-school participants become injured and seek medical treatment at an annual cost close to $2 billion. The purpose of the current study was to evaluate the injury incidence and rates in female athletes in the middle-school setting during the course of 3 seasons.Methods:Female basketball, soccer, and volleyball players were recruited from a single county public school district in Kentucky consisting of 5 middle schools. A total of 268 female athletes (162 basketball, 26 soccer, and 80 volleyball) participated. Athletes were monitored for sports-related injury and number of athlete exposures (AEs) by an athletic trainer. Injury rates were calculated for specific types of injuries within each sport. Injury rates for games and practices were also calculated and compared for each sport.Results:A total of 134 injuries were recorded during the 3 sport seasons. The knee was the most commonly injured body part (99 injuries [73.9%]), of which patellofemoral dysfunction (31.3%), Osgood-Schlatter disease (10.4%), and Sinding-Larsen-Johansson/patella tendinosis (9%) had the greatest incidence. The ankle was the second most commonly injured body part, accounting for 16.4% of all injuries. The overall rates of injury by sport were as follows: soccer, 6.66 per 1000 AEs; volleyball, 3.68 per 1000 AEs; and basketball, 2.86 per 1000 AEs.Conclusions:Female middle-school athletes displayed comparable injury patterns to those seen in their high-school counterparts. Future work is warranted to determine the potential for improved outcomes in female middle-school athletes with access to athletic training services.Clinical Relevance:As the participation levels and number of injuries continue to rise, middle-school athletes demonstrate an increasing need for medical services provided by a certified athletic trainer.